Jazz et aspirations collectives : un « call-response » inversé ? - Philippe Sadikalay (Études Caribéennes)
The principle of antiphony, more commonly known as "call-response" is often mentioned in the contextual configuration of an artistic expression, whether literary, as in Toni Morrison’s novels for example, or in music, in most cases. It represents the process that will frame and format the modalities of communication between members of an audience and a performer, a creator. This article proposes a broader and cross-reading approach of this typical habitus among black communities in the Americas, especially in contemporary contexts of the Civil Rights Movements and of the aesthetic renewal of Jazz, after the Swing era.